A hybrid acoustic structure for low-frequency and broadband underwater sound absorption. Issue 3 (September 2022) - Jia, Xinyu; Jin, Guoyong; Shi, Kangkang; Bu, Chunyang; Ye, Tiangui
The underwater anechoic coating with local resonant units is an effective method to achieve low-frequency sound absorption. However, the structure obtained in this way is not satisfactory in the sound absorption effect of mid-high frequency bands. Capitalizing on the impedance gradient characteristics of functionally graded materials (FGMs) can improve the impedance matching between the structure and the medium, and enhance the dissipation of sound waves inside the structure. Based on these, we propose an underwater acoustic structure, which can improve and obtain low-frequency and broadband sound absorption performance by embedding local resonators into FGMs. To reveal the sound-absorbing mechanism and further optimize the low-frequency absorption performance of the structure, we conduct quantitative analyses on the parameters of FGMs, the materials and forms of resonators. The results indicate that by appropriately adjusting the studied parameters, different low-frequency sound-absorbing peak can be obtained and the absorption effects are also further improved.